1998
DOI: 10.1262/jrd.44.79
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Stimulation by Prostaglandin F2.ALPHA. Involves the Protein Kinase C Pathway in Cultured Bovine Luteal Cells.

Abstract: Abstract. The intracellular mechanism that mediates the stimulatory effect of prostaglandin F2α (PGF2α) on progesterone secretion by bovine luteal cells is not well understood. In the present study, we investigated to test the hypothesis that PGF2α stimulates progesterone secretion through activation of protein kinase C (PKC) by using a cell culture system. Bovine mid-luteal cells (Days 8-12 of the estrous cycle) were cultured for 24 h and then exposed to varying concentrations of PGF2α (10 -8 , 10 -7 , 10 -6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 31 publications
(41 reference statements)
8
70
0
Order By: Relevance
“…Thus, the dominant intracellular mechanisms involved in the action of PGF2α is the activation of the PKC cascade in bovine luteal cells. Indeed, recent data from bovine CL cells in culture showed a lack of P stimulation in PKC-deficient cells [8]. The present in vivo data are consistent with the above findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the dominant intracellular mechanisms involved in the action of PGF2α is the activation of the PKC cascade in bovine luteal cells. Indeed, recent data from bovine CL cells in culture showed a lack of P stimulation in PKC-deficient cells [8]. The present in vivo data are consistent with the above findings.…”
Section: Discussionsupporting
confidence: 93%
“…In these in vitro studies, PGF2α clearly activated intracellular mechanisms involved in the cascade of stimulation of protein kinase C (PKC) [3][4][5] and free calcium ion (Ca 2+ ) [4][5][6][7]. Recently, it has been further demonstrated that PGF2α failed to stimulate the release of P from PKC-deficient bovine luteal cells, suggesting that the luteotropic action of PGF2α is mediated by the activation of intracellular PKC in culture [8]. These results support the hypothesis that luteal PGF2α may have a dual function (luteotropic in young CL, but luteolytic in aged CL).…”
mentioning
confidence: 99%
“…Based on an in vitro study (Speroff & Ramwell 1970), a direct PGF steroidogenic stimulation of luteal cells has been suggested (Hixon & Hansel 1974). Direct inhibitory and stimulating effects of PGF on small and large luteal cells respectively have been demonstrated in vitro (Alila et al 1988, Meidan et al 1992, Girsh et al 1995, Okuda et al 1998, Skarzynski & Okuda 1999. In addition, the results of studies involving treatment with a bolus luteolytic dose of PGF have been interpreted to indicate that nitric oxide is a crucial factor in initiating luteolysis through a drastic increase in luteal blood flow (Shirasuna et al 2008), and that the induced increase in luteal blood flow is the first step in the luteolytic cascade (Miyamoto et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al [10,11] indicated that a high fat diet causes increased frequency of luteal activity and alterations in specific aspects of ovarian steroidogenic potential. Other researchers have shown that PL activates protein kinase, which controls luteal cells [12,13], and that lipoprotein, which is composed of PL, regulates P4 production in luteal cells [14,15].…”
Section: Discussionmentioning
confidence: 99%